Discretion vs. Uniformity: Choices among GAAP - Dye, Ronald A.; Verrecchia, Robert E. (The Accounting Review, 1995)
[We reexamine the "uniformity vs. flexibility" debate by considering the consequences of varying the amount of discretion managers have in reporting current period expenses. We study the effects of altering GAAP on both the "internal agency problem" between current shareholders and their manager and the "external agency problem" between current and prospective shareholders. We show that the internal agency problem is ameliorated by expanding discretion, and we exhibit examples where expanding discretion is undesirable when the internal and external agency problems are present concurrently and the nonexpense-related components of earnings are measured with error. We establish that expanding discretion is welfare-enhancing if either the manager's contract is publicly observable or else the nonexpense-related components of earnings are measured without error. These results demonstrate the limitations of evaluating GAAP on a piecemeal, or issue-by-issue, basis.]